Synthesis of carbon nanowalls by the method of plasma enhanced chemical vapor deposition in a radio-frequency discharge plasma - Yerlanuly, Ye.; Batryshev, D.G.; Hori, M. (Recent Contributions to Physics, 2019)
The work is devoted to the synthesis of carbon nanowalls (CNWs) by the method of plasma enhanced chemical vapor deposition in a radio-frequency (RF) discharge plasma at various values of RF discharge power and the study of their properties. As a result of the study, the optimum power parameter for growth of CNWs with perfect structure was determined. It has been established that a further increase in power leads to the agglomeration of nuclei of the CWNs and the formation of nanoclusters and a multilayer graphene structure, which is evidenced by the microscopic analysis of the samples. The morphology and structure of the CNWs were studied by using a Quanta 3D 200i scanning electron microscopy (SEM, the FEI company, USA) and Ntegra SPECTRA Raman spectroscopy. It has been established that the ion irradiation of Ar plays an important role in the mechanism of the formation of the CNWs. Irradiation with Ar ions enhances the surface reaction in the growth phase, including the adsorption of hydrocarbon radicals on dangling bonds (defects), while an increase in ion irradiation (increase in RF power) impedes further vertical growth of carbon nanostructures due to the etching effects. This phenomenon explains the emergence of agglomerated CNWs with increasing discharge power.